Design and Kinematics Simulation of a Wire-driven Multi-section Continuous Manipulator - Wei Guiwei; Xu Zhenbang; Zhao Zhiyuan; Yu Yang; Wu Qingwen (Jixie chuandong)
In order to satisfy the requirements of complex space environment， a wire-driven multi-section continuous manipulator is designed. A simple modeling method for wire-driven continuous manipulators is presented based on geometric analysis method. The mapping relationship between joint space，driving space and operation space of the single section flexible joint are analyzed，and a decoupling kinematics algorithm for three sections manipulator is given. The manipulator workspace is described using improved Monte Carlo method. The kinematics simulation of the manipulator is carried out by using Matlab. The correctness of the kinematics algorithm is verified by the experimental study of the principle prototype，and the good bending ability of the manipulator is demonstrated.